2007
DOI: 10.1097/meg.0b013e32812144dd
|View full text |Cite
|
Sign up to set email alerts
|

Capsule enteroscopy vs. other diagnostic procedures in diagnosing obscure gastrointestinal bleeding: a cost???effectiveness study

Abstract: Capsule enteroscopy is a cost-saving approach in the evaluation of patients with obscure gastrointestinal bleeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
9

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 21 publications
0
25
0
9
Order By: Relevance
“…Therefore, in many countries the need for an examination in the diagnostic algorithm of OGIB that combines the high diagnostic yield with cost-effectiveness is more pertinent than ever. VCE has been shown to be an economically sound testing strategy (56,60). Considering its high NPV, patients with negative VCE reasonably undergo no further diagnostic work-up; minimizing procedural costs on the long-term (55,56).…”
Section: Impact On Subsequent Therapeutic Strategies and Clinical Outmentioning
confidence: 99%
“…Therefore, in many countries the need for an examination in the diagnostic algorithm of OGIB that combines the high diagnostic yield with cost-effectiveness is more pertinent than ever. VCE has been shown to be an economically sound testing strategy (56,60). Considering its high NPV, patients with negative VCE reasonably undergo no further diagnostic work-up; minimizing procedural costs on the long-term (55,56).…”
Section: Impact On Subsequent Therapeutic Strategies and Clinical Outmentioning
confidence: 99%
“…General consensus today is that early diagnosis by CE can be followed by DBE findings, combined with interventional enteroscopy by the same method. (Kameda N et al, 2008;Marmo R et al, 2007) 6.2 Capsule endoscopy in Crohn's disease In Crohn's disease, patients often experience pain, diarrhea and weight loss, non-specific symptoms that do not correlate with the negative results from usual imaging investigations. (Kornbluth A et al, 2005) A consensus panel suggested that further investigation by CE is useful when patients display at least two of these symptoms.…”
Section: Diagnostic Yield Comparison With Other Investigations and mentioning
confidence: 99%
“…(Marmo R et al, 2007;Oradei et al, 2005) DBE and CE are considered complementary, initial DBE proved to be more cost effective; however CE followed by DBE was more cost-effective if DBE showed a probability below 59% of angiectasia. (Dyer S et al, 2004;Kamal A et al, 2006) …”
Section: Capsule Endoscopy: Cost Effectivenessmentioning
confidence: 99%
“…D'autre part, des études récentes [25,26] se sont attachées à évaluer le rapport coût et efficacité d'une telle stratégie basée sur l'utilisation d'une capsule endoscopique suivie d'une entéroscopie double ballon. L'une de ces études montre un coût plus élevé de cette double approche mais avec une incidence favorable sur le nombre de patients décédés du fait de la pathologie primitive ou de complications des examens diagnostiques [25].…”
Section: Données De La Littératureunclassified